2023
DOI: 10.3389/fonc.2023.1105778
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of autophagy-related clusters and individual risk model for immunotherapy response prediction in gastric cancer

Abstract: IntroductionAutophagy can be triggered by oxidative stress and is a double-edged sword involved in the progression of multiple malignancies. However, the precise roles of autophagy on immune response in gastric cancer (GC) remain clarified.MethodsWe endeavor to explore the novel autophagy-related clusters and develop a multi-gene signature for predicting the prognosis and the response to immunotherapy in GC. A total of 1505 patients from eight GC cohorts were categorized into two subtypes using consensus clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…who performed a genetic screening on several cancer cell lines treated with Bispecific T-cell engagers and revealed that a change of autophagy-related genes is involved in their limited anti-tumor effect [ 204 ]. They and others also demonstrate how autophagy pathways could be shaped by tumor cells following therapies, for example, predisposing the generation of a cold tumor microenvironment [ 205 207 ].…”
Section: Potential Clinical Application For Adoptive Cell-therapymentioning
confidence: 99%
“…who performed a genetic screening on several cancer cell lines treated with Bispecific T-cell engagers and revealed that a change of autophagy-related genes is involved in their limited anti-tumor effect [ 204 ]. They and others also demonstrate how autophagy pathways could be shaped by tumor cells following therapies, for example, predisposing the generation of a cold tumor microenvironment [ 205 207 ].…”
Section: Potential Clinical Application For Adoptive Cell-therapymentioning
confidence: 99%
“…Additionally, it is well-recognized that oxidative stress can initiate autophagy. Yao et al attempted to investigate novel autophagy-related clusters and create a multi-gene signature for GC that could predict prognosis and immunotherapy response [184]. Using consensus clustering, a total of 1505 individuals from eight GC cohorts were divided into two subgroups.…”
Section: Gastric Cancermentioning
confidence: 99%